2009
DOI: 10.1002/clc.20668
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Peripheral Arterial Tonometry in the Measurement of Endothelial Function in Healthy Men

Abstract: Measurement of endothelial function using peripheral arterial tonometry (PAT) has been reported to be significantly correlated with coronary blood flow. Repetitive PAT measurements were performed in 22 healthy male subjects at test intervals of 1 hour (5 times within a day) and 0.5 hours (7 times within a day) to evaluate the variability of the reactive hyperemia index (RHI). A total of 10 subjects underwent additional repetitive PAT at 2 hour intervals (7 times within a day) for 3 consecutive days to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 17 publications
9
48
0
Order By: Relevance
“…At the baseline visit, the RH-PVA was 2.0, a result similar to what has been observed previously in healthy populations [20]. Baseline endothelial function was not different between the losartan- and placebo-treated subjects (Table 3).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…At the baseline visit, the RH-PVA was 2.0, a result similar to what has been observed previously in healthy populations [20]. Baseline endothelial function was not different between the losartan- and placebo-treated subjects (Table 3).…”
Section: Resultssupporting
confidence: 86%
“…In contrast, Koh et al [42] found that each of losartan, candesartan and irbesartan improved FMD (flow-mediated dilation) of the brachial artery compared with placebo in patients with mild-to-moderate essential hypertension. We did not detect an effect of ARB therapy on endothelial function measured by RH-PVA; however, our subjects’ RH-PVA response prior to intervention was similar to that reported previously in healthy subjects [9,20,43]. Although the present study did not have an internal control group of healthy individuals, these historical data suggest that our selection criteria did not effectively identify a group of subjects with endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, though a significant association was found between radial PTT and age, the information from radial PTT could not be expected to be identical to PWV, for the shape of the radial pulse was influenced by various factors. [28][29][30] In summary, PTT obtained directly from radial arterial waveforms was significantly associated with age in healthy adult with a wide age range. The effect of HR changes on radial PTT was insignificant until it was up to 80 b.p.m.…”
Section: Discussionmentioning
confidence: 82%
“…Research confirmed the effect of diurnal variation [123] and the effect of dietary components such as omega-3 fatty acids [27], polyphenol rich olive oil [124], chocolate [125], and tea [126]. Furthermore, measurements were influenced by drugs [81] and mental stress [127].…”
Section: Peripheral Arterial Tonometrymentioning
confidence: 91%